SOCIAL ANTICIPATION REDUCES PAST FRAUD'S EFFECT ON WHISTLEBLOWING INTENTIONS - Endah, Sih Mirmaning Damar; Stephana Dyah Ayu Ratnaningsih; Stefani Lily Indarto (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes A new model related to the influence of prior cheating experience on one's intention to whistleblowing by using anticipatory socialization and attitude as intervening and moderating variables, that can reduce the negative impact of previous cheating on whistleblowing intention. Research Method This study aims to determine how to reduce the influence of prior cheating experience on a person's whistleblowing intention by adding the role of anticipatory socialization as a moderating variable and attitude as an intervening variable. Survey method used with 703 accounting students in Semarang, Indonesia as sample. Testing was carried out using the Path Analysis Model. Research Results and Findings The result indicates that prior cheating experience, attitude, and social anticipation affect a person's intention to whistleblowing. Anticipatory socialization, as a moderating variable, and attitude, as an intervening variable, lower the intention to whistleblowing. Higher education leaders should provide characteristics of accountant professionals as a fundamental material to increase students’ socialization anticipation. Norm clarity is expected to increase a person's social anticipation. Therefore, company’s ethical standards or codes of conduct that support whistleblowing is needed.